A higher JAK2V617F allele burden may be a risk factor for hemorrhagic events in younger patients with polycythemia vera - Chiho Furuya; Yoshinori Hashimoto; Soji Morishita; Yasutaka Fukuda; Tadaaki Inano; Tomonori Ochiai; Shuichi Shirane; Yoko Edahiro; Marito Araki; Miki Ando; Norio Komatsu (Hematology)
Objectives: Hemorrhagic events are a rare but potentially fatal complication in patients with polycythemia vera (PV).Methods: We analyzed the characteristics of hemorrhagic events in 267 patients with PV.Results: A median follow-up of 4.8 years revealed that 23 (8.6%) hemorrhagic events occurred. Significantly more hemorrhagic events occurred in younger patients aged below 60 years (n = 72) than in older patients aged 60 years or above (n = 191) (n = 12 [16.7%] vs. n = 11 [5.8%], respectively, P = 0.012). In univariate analysis among the younger patients, white blood cell (WBC) count ≥ 15 × 109/L (hazard ratio [HR] = 7.746, 95% confidence interval [CI] 2.082-28.830, P = 0.002), palpable splenomegaly (HR = 5.629, 95% CI 1.193–26.550, P = 0.029), and JAK2V617F allele burden ≥ 80% (HR = 22.850, 95% CI 2.885–181.00, P = 0.003) were associated with an increased risk of hemorrhagic events. In multivariate analysis, JAK2V617F allele burden ≥ 80% (HR = 9.394, 95% CI 1.046–84.380, P = 0.046) was a significant risk factor.Conclusions: There is an increased risk of hemorrhagic events after diagnosis in younger PV patients with a high JAK2V617F allele burden, high WBC count or palpable splenomegaly. It is important to consider treatment options that aim to avoid hemorrhagic events by reducing the JAK2V617F allele burden in younger PV patients.